CREATIVITY AND CONVERGENT THINKING: REFLECTIONS, CONNECTIONS AND PRACTICAL CONSIDERATIONS - Lubart, Todd (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2016)
Creativity is conceived as the ability to generate new, original ideas that are meaningful and valuable in their context. Models have often debated the role of divergent and convergent thinking within creativity. This paper focuses on convergent thinking and examines ways that it has been conceptualized and operationalized. It is noted that some of these conceptualizations fit more than others with creative thinking. Finally, examples of new ways to measure convergent thinking for creativity are presented and explained. The Evaluation of Potential Creativity (EpoC) battery is described as a relevant new tool to assess convergent thinking, with a focus on the integrative, original synthesis, which is ultilmately essential to the creative process, and the potential for resulting creative productions. Implications for measuring creativity and education are discussed.